Weaving participation, interaction, and technology across recreational experiences: perspectives from volunteers, caregivers, and people with complex communication needs. (3rd July 2019) - Hajjar, David J.; McCarthy, John W.; Benigno, Joann P.; Montgomery, James; Chabot, Jennifer; Boster, Jamie
Abstract: Recreational and leisure activities offer many meaningful and motivating opportunities for communication and improving quality-of-life. Volunteers in recreation activities have important roles as participation and communication facilitators, while also creating opportunities for learning and social interaction. The aim of this study was to implement a novel photo and video intervention called the CAPTURE & Share Program, and to evaluate its impact on communication opportunities and participation. For the study, five volunteers were assigned to five individuals with complex communication needs. Each dyad took photos and videos during a series of three kayaking lessons. After each lesson, volunteers participated in feedback sessions, while caregivers, support staff, and participants with complex communication needs shared their perspectives during pre- and post-lesson interviews. A thematic analysis, based on the data from the volunteer feedback sessions, revealed five primary themes: Program Components, Modifications, Barriers, Supports, and Benefits. Findings revealed that volunteers supported the individuals with complex communication needs who participated in the study to collect photos and videos as they learned how to use cameras and communicate their preferences for capture. Furthermore, the photos and videos that were collected were shared with family and friends, which encouraged more frequent social interactions and opportunities for communication. Findings suggest that recreational activities were perceived to provide an appropriate infrastructure for photo and video capture and to support opportunities for communication.